(untitled) (The Strategic Review for Southern Africa, 2021)
This article traces the limits of branding as a tool for (re)constructingnations as 'imagined communities' (Anderson 1983). Drawing on examples from post-socialist Eastern Europe, I analyse discourses and practices of nation branding from a critical perspective, rooted in the theoretical traditions of political economy and cultural studies. Focusing more closely on branding campaigns implemented by post-Soviet Ukraine and post-war Kosovo — two nations seeking to assert themselves as independent actors on the global stage — I consider the impact of nation branding on national identities and democratic governance. I identify three interconnected limits of the branded national imagination as a structuring discourse for nation building. First, the branded national imagination is structured through its subjection to a foregin gaze; second, it is heavily dependent on commercial transnational media; and third, it produces branded national subjectivities that contradict the lived experiences of national populations. I argue that while nation branding effectively depoliticises national (re)definition, it may in fact serve to reinvigorate ethnic nationalisms in the post-socialist region. Finally, I suggest that although we must be aware of local histories and legacies, the post-socialist experience can inform our understanding of the structuring limits of the branded national imagination in other post-conflict and post-colonial contexts as well.